Development of Werewolf Game Media To Improve Students' Social Skills - Wanda Afiffah; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (Program Studi Bimbingan dan Konseling, 2025)
The research is based on the low social skills of students, especially at SMAN 4 Kota Serang, as found that students only socialize with their group friends, are passive when discussing, passive when friends need help and do not accept reprimands from friends. Efforts made to improve students' social skills include playing games. One of the potential games to utilize is the werewolf game. This study, therefore, aims to enhance social skill through the development of werewolf game-based media. The research employs a research and development (R&D) approach, using the Thiagarajan 4D model, which includes the stages of define, design, develop, and dissemination. The results of the study obtained from the product feasibility test obtained an average score of 86% with the category